Synthesis of ZrB2 Powders from ZrO2, BN, and C. Issue 1 (25th November 2015) - Yan, Chunlei; Liu, Rongjun; Zhang, Changrui; Cao, Yingbin; Long, Xianhai
Abstract : Submicrometer (200–800 nm) ZrB2 powders have been successfully prepared via a new ZrO2 –C–BN precursor powder system at a relatively low temperature (1550°C) for 1.5 h. As a moderate cost boron source, BN has a well‐defined stoichiometry and low impurity. Both thermodynamic and experimental results indicated that ZrC was formed below 1300°C, a temperature required for ZrB2 formation. Moreover, the reaction of ZrC–BN mixture at 1300°C indicated that the ZrC acted as an effective direct reducing reagent for BN to form ZrB2, indicating that the pathway involving the formation of intermediate phase ZrC determined the formation mechanism.